Silence or Sanism: A Review of the Dearth of Discussions on Mental Illness in Adult Education. Issue 2 (April 2017) - Procknow, Greg
Abstract: This literature review engages mental illness in adult education (AE) to locate what research exists and to suggest a research agenda moving forward. This structured review located research related to mental health issues published in the conference proceedings of the Canadian Association for the Study of Adult Education (CASAE) and the Adult Education Research Conference (AERC) and fourteen international AE journals. AE scholarship focused on identity construction, andragogy and classroom issues, public pedagogy, popular education and arts‐based education, contesting psychiatric knowledge and sanism, and workplace.